Assortative Mating and Earnings Inequality in France. (15th December 2019) - Frémeaux, Nicolas; Lefranc, Arnaud
Abstract : This paper analyzes assortative mating and its contribution to inequality in France. We first provide descriptive evidence on the statistical association in several socio‐economic attributes of partners. Second, we assess the contribution of assortative mating to earnings inequality between couples. We provide a new method for assessing the contribution of assortative mating to inequality in couple's potential earnings, that accounts for selection bias arising from labor force participation. Our results indicate a strong degree of assortative mating in France. The correlation in earnings is around 0.17 for annual earnings, around 0.35 for full‐time equivalent earnings and up to 0.49 when using multi‐year average earnings. Assortative mating tends to increase inequality among couples. For annual earnings, the effect accounts for 3 to 9 percent of measured inequality. The effect of assortative mating on household potential earnings is much larger and amounts to 10 to 20 percent for observed inequality.